Public Perceptions of Deer Management in Scotland - Hare, Darragh; Daniels, Mike; Blossey, Bernd (Frontiers in Conservation Science, 2021)
In Scotland, large deer populations are associated with negative ecological and socioeconomic impacts, such as damage to peatlands and forests, agricultural and commercial forestry losses, Lyme disease transmission, and road accidents. Increasing the annual deer cull might help address these negative impacts, but could be ethically controversial. A stratified sample of adults living in Scotland (n = 1002) responded to our online questionnaire measuring perceptions of deer management, including the acceptability of increasing the deer cull if doing so would help achieve a variety of ecological and social objectives. Overall, respondents indicated that it would be acceptable to increase the deer cull if doing so would serve public interests by reducing negative impacts of deer, with deer welfare and environmental conservation being the most relevant ethical considerations. Although rural and urban respondents reported significantly different experiences and perceptions of deer, their attitudes and policy preferences regarding deer management did not significantly differ. Understanding values of the general public, beyond vocal interest groups, can inform decisions on contentious wildlife management issues.